Gender dynamics, biodiversity, collective thinking: Key elements of the WEFE approach - McCartney, Matthew P.; Ringler, Claudia (CGIAR, 2024)
Gender dynamics play a crucial role within the water–energy–food–ecosystems (WEFE) nexus, as women often have different roles and responsibilities related to water, energy, and food production. Moreover, in many contexts, women are disproportionately affected by water scarcity, lack of access to clean energy, and food insecurity. However, most emerging nexus approaches have been narrowly focused on resource efficiency and technocratic ‘fixes’ that do not adequately consider the impacts of resource use and development on women. Typically, these approaches fail to ask who these nexus innovations are serving: who makes decisions, on whose behalf? Who does the work, who bears the risks or costs, and who reaps the benefits?